Prophylactic intranasal alpha 2 interferon and viral exacerbations of chronic respiratory disease. Issue 10 (October 1991) - Wiselka, M J; Nicholson, K G; Kent, J; Cookson, J B; Tyrrell, D A
Abstract : BACKGROUND As respiratory virus infections often lead to exacerbations of chronic bronchitis and asthma an effective antiviral drug may be helpful in such patients. Alpha 2 interferon has been shown to give protection against rhinovirus infections in field studies. METHODS Patients with chronic respiratory disease exposed to close contacts with symptoms of upper respiratory tract infection were randomly allocated to receive nasal sprays of recombinant alpha 2 interferon (3 x 10(6) IU) or placebo twice daily for five days. Of the 123 patients recruited into the study, 69 took 117 courses of medication; 11 courses were excluded from analysis. RESULTS No important side effects were recorded and the incidence of possible adverse effects was similar in the two groups. Interferon treatment did not reduce the number or severity of symptomatic episodes; 11 of 48 patients given interferon and 16 of 58 given placebo developed lower respiratory symptoms. There were no differences in mean symptom scores (51 interferon and 52 placebo), number of symptomatic days (3.3 interferon and 5.0 placebo), peak flow values, number of general practitioner consultations, or use of antibiotics. CONCLUSION Alpha 2 interferon 3 x 10(6) IU taken twice daily for five days does not protect patients with chronic respiratory disease from exacerbations after they have been in contact with an upper respiratory tract infection.